PENGARUH POSISI PERSALINAN TERHADAP DERAJAT RUPTUR PERINEUM PADA IBU BERSALIN - Rofi?ah, Siti; Iswara, Popi Nurbaeti (Jurnal Kesehatan Ibu dan Anak, 2014)
Based on World Health Organization ( WHO) data in 2009 there were 2,7 millions ruptur perineumcases. This numbers will be predicted 6,3 millions in 2050. One of the causes for morbidity and mortality mother is any infection during puerperium in which that infection firstly happens in rupturperineum when delivering the baby. Birth is a fisiologic event in normal life. There are several pushing positions in delivered mother kala II. One of them is a half sitting positon that gives acomfort condition for mother in supplying oxygen from mother to infant normally and other is a squating position that uses body gravitation so the baby can be delivered easily without pushing,because of that the researcher intents to know is there any influence for pushing position toward ruptur perineum level for delivered mother. The research aims to know the influence of position toward the ruptur perineum level. The kind of the research is a quasy experiment with prospectiveapproach and the location of the research is in Mojotengah Public Health Center. The sampling istaken from 60 populations in each treatment with purposive sampel . The data has been analyzedby univariat in percentage and bivariat analysis with mann whitney test. The research result shows that there is an influence between the half sitting position toward the ruptur perineum levelwith significant score or p value 0,015. Midwife suggests the women to take half sitting position indelivering the baby to avoid the number of ruptur perineum.